(untitled) (Research, Society and Development, 2021)
Within a society, social capital is in the social networks’ structures, which, in turn, establish lasting relationships between actors, through precepts such as reciprocity and reliability that facilitates actions such as the formation of councils that seek collective resources for the community. This study aims to identify the actions of the Council, the meaning of social participation and its implications in the construction of a participatory-democratic model. The methodology used is based on the case study of the Economic and Social Development Council of Nova Serrana - MG. Documental analyses and semi-structured interviews were carried out. As a result, it was possible to verify that the Council’s actions are linked to the areas of health, security, education, infrastructure, and articulation between the Executive and Legislative branches. It was concluded that the Council is an important instrument for the expansion of participatory-democratic freedom, which reinforces the effective social participation of social actors. To the same extent, it promotes and strengthens social capital. All these actions have resulted in the strengthening of the Council itself, and in the economic and social development of the municipality.